Kebijakan ICJ Dalam Penyelesaian Sengketa Perbatasan Kawasan Sekitar Kuil Preah Vihear Tahun 2008–2011 - Prabandari, Ni Made Media; Resen, Titah Kawitri; Parameswari, A.A. Ayu Intan (DIKSHI (DISKUSI ILMIAH KOMUNITAS HUBUNGAN INTERNASIONAL), 2020)
ABSTRACT In supporting efforts to bring about peace, ICJ always strives to provide the best solutions for countries that are involved in conflict. For example Thailand and Cambodia in a territorial disputes. This research will look at how ICJ through the PDZ mechanism helped Thailand and Cambodia to reach a point of peace after the conflict since the crowning of the historic Preah Vihear temple in 2008 by UNESCO, in 1962 the temple was legitimately owned by Cambodia but the ownership of the area around the temple is not yet clear. This research uses descriptive qualitative research using the concept of the role of international organizations. This concept analyzes ICJ policy and ASEAN's involvement as a mediator. Then it was found that the policies of the ICJ through the formation of the PDZ were able to encourage the two countries to stop armed clashes until finally finding a point of peace. Keywords : Thailand-Cambodia, ICJ, ASEAN, Conflict